2022
DOI: 10.1038/s41598-022-08808-7
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial effect of cell-free supernatant fraction from Lactobacillus paracasei CH88 against Gardnerella vaginalis

Abstract: Bacterial vaginosis (BV) is the most common vaginal infection in reproductive women, which is characterized by depleted level of lactic acid bacteria and overgrowth of anaerobes such as Gardnerella vaginalis spp. Lactic acid bacteria have been known to be beneficial for amelioration of BV, since they produce antimicrobial substances against G. vaginalis spp. The objectives of this study were to characterize different fractions of cell-free supernatant of Lactobacillus paracasei CH88 (LCFS) and investigate anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Interestingly, the CFS of HY7801 did not significantly inhibit GV biofilm formation (Fig. 3B), unlike previous studies that showed that the CFS of specific probiotics inhibited GV biofilm formation (Moon et al, 2022;Qian et al, 2021). Therefore, in order to exclude the effects of lactic acid and H 2 O 2 , GV and HY7801 were co-cultured in fresh media, and the expression of GV virulence factor genes related to immune avoidance, epithelial cell attachment, biofilm formation, and energy metabolism was confirmed.…”
Section: Resultsmentioning
confidence: 56%
See 2 more Smart Citations
“…Interestingly, the CFS of HY7801 did not significantly inhibit GV biofilm formation (Fig. 3B), unlike previous studies that showed that the CFS of specific probiotics inhibited GV biofilm formation (Moon et al, 2022;Qian et al, 2021). Therefore, in order to exclude the effects of lactic acid and H 2 O 2 , GV and HY7801 were co-cultured in fresh media, and the expression of GV virulence factor genes related to immune avoidance, epithelial cell attachment, biofilm formation, and energy metabolism was confirmed.…”
Section: Resultsmentioning
confidence: 56%
“…Vaginal epithelial cell exfoliation, a major clinical feature of BV, has been reported to be associated with increased transitional epithelial proliferation of the vagina (Bautista et al, 2016;Moon et al, 2022). Therefore, the effect of HY7801 on histological changes of vaginal tissues in GVinfected BV mice was investigated through histopathological analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of approaches for controlling antibiotic-resistant pathogens, a spectrum of strategies is being investigated, from novel antibiotic development to phage therapy. However, there has been increasing attention on the utilization of probiotics, notably Lactobacillus strains, in this context 15,40,41 . This focus is substantiated by the generally safe pro le of Lactobacillus, its minimal side-effects, and its capacity to modulate both microbial antagonism and host immune response 11 .…”
Section: Discussionmentioning
confidence: 99%
“…polysaccharides, proteins, fatty acids, peptides, and organic acids) are biologically active molecules that often optimize physiological and immune functions of the host and provide numerous benefits. Cell-free supernatants of lactobacilli have frequently been shown to possess antimicrobial properties due to the presence of organic acids and bacteriocins ( Yang et al, 2021 ; Moon et al, 2022 ). The supernatants obtained from the growth of L. brevis SP 48 were here investigated to study the effects of a polysaccharide- and protein-enriched secreted fraction, deprived of organic acids and bacteriocins removed by ultrafiltration.…”
Section: Discussionmentioning
confidence: 99%